ANALYSIS OF LOGISTIC MANAGEMENT OF DRUG STORAGE IN PHARMACIES - Rochana Ruliyandari; Ahmad Ahid Mudayana; Kartika Lestari; Fanny Ariesca; Shafira Cahya Afita; Attiro Rahmadani (Yayasan Education and Social Center, 2023)
One of the stages in managing the logistics of drugs is storage. Drug storage is an activity that involves storing and maintaining drugs with the goals of preserving drug quality, preventing irresponsible use of drugs, and making it easier to search for and control drugs. This study analyzes the logistics management of drug storage in pharmacies in 2022. This research is an analytic descriptive study with a qualitative approach. Data was gathered through direct interviews with informants, including pharmacists and pharmacist assistants. The findings revealed some differences and similarities between pharmacies based on 12 criteria for drug storage. The criteria for storing these drugs include drugs stored in a special warehouse, drugs stored not mixed with other equipment, medicines placed on shelves/pallets indirectly on the floor, medications kept in doses from delivery, treatments separated by dosage form, pills arranged alphabetically, medicines are stored according to drug class (medicine for general, moderate, severe diseases), medicines that require cold temperatures stored in a refrigerator or cold chain, narcotics, and psychotropics are stored in a special cupboard and locked, storage of drugs uses the FIFO and FEFO systems, what is done for drugs that are near their expiration date, and what is done for drugs that have expired. All of the samples, which include thirty-six pharmacies, have stored medications on shelves or pallets and indirectly on the floor, have stored medicines by the dosage forms, and have stored drugs using the FIFO and FEF systems